(untitled) (Bioscience Journal, 2018)
This research aimed to evaluate the dry matter yield, structural composition and nutritive characteristics of diploid and tetraploid annual ryegrass cultivars on different phenological development to haymaking on lowland soils. The experimental design was developed based on randomized blocks with split plots, four cultivars of annual ryegrass (BRS Ponteio and FEPAGRO São Gabriel, diploid; INIA Escorpio and KLM 138, tetraploid), and three phenological crop phases (vegetative, pre-blossoming and blossoming). Were evaluated, dry matter yield, leaf:stem ratio, leaf weight ratio, tiller population density, specific leaf area, crude protein, neutral detergent fiber, and acid detergent fiber. All data were submitted to analysis of variance and the means were compared by Tukey-Kramer test (p< 0,05). Highest forage mass is obtained with harvest in blossoming stage. Tetraploid cultivars present better leaf proportion and higher content of crude protein during vegetative stage. The decrease the in concentration of protein with the change of phenological stage is less evident on diploid cultivars. The vegetative stage enables harvest forage with high nutritional value, with lower production of biomass.